Influence of concentration and order of aggregation of the active phases in V-Mo-O catalysts in the oxidative dehydrogenation of propane - Murgia, Viviana (2008)
The activation of alkanes by oxidative route is an alternative way to obtain products with greater added value. The mixed catalysts obtained by impregnation of Mo and V on different supports conform a potentially attractive system to achieve dehydrogenation of propane. The activity and selectivity depend on the Mo/V ratio used. In this work, we have studied the effect of the concentration and the order of incorporation of the active phases on the catalytic behavior and the nature of the acid sites on the catalyst surface for this reaction. Catalysts with weight contents of 1.4 and 2.8% of vanadium and/or 4 and 8% of molybdenum were prepared. The results show that for solids with low vanadium load the order of aggregation of the active phases does not modify the catalytic behavior. When vanadium load increases, greater conversion is observed when molybdenum is incorporated in the first place. This behavior can be related to the formation of Mo-V-O species. The catalytic properties are also influenced by the nature and strength of the acid sites on the surface. © 2008.